(untitled) (European Journal of Pure and Applied Mathematics, 2020)
The aim of this paper is to introduce the notions of relatively deferred Norlund uniformÂ statistical convergence as well as relatively deferred Norlund point-wise statistical convergenceÂ through the dierence operator of fractional order of fuzzy-number-valued sequence of functions,Â and a type of convergence which lies between aforesaid notions, namely, relatively deferred NorlundÂ equi-statistical convergence. Also, we investigate the inclusion relations among these aforesaid notions. As an application point of view, we establish a fuzzy approximation (Korovkin-type)Â theorem by using our new notion of relatively deferred Norlund equi-statistical convergence andÂ intimate that this result is a non-trivial generalization of several well-established fuzzy Korovkin-typeÂ theorems which were presented in earlier works. Moreover, we estimate the fuzzy rate ofÂ the relatively deferred Norlund equi-statistical convergence involving a non-zero scale function byÂ using the fuzzy modulus of continuity.